2018
DOI: 10.1038/s41598-018-20588-7
|View full text |Cite
|
Sign up to set email alerts
|

Stationary gaze entropy predicts lane departure events in sleep-deprived drivers

Abstract: Performance decrement associated with sleep deprivation is a leading contributor to traffic accidents and fatalities. While current research has focused on eye blink parameters as physiological indicators of driver drowsiness, little is understood of how gaze behaviour alters as a result of sleep deprivation. In particular, the effect of sleep deprivation on gaze entropy has not been previously examined. In this randomised, repeated measures study, 9 (4 male, 5 female) healthy participants completed two drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 50 publications
0
69
0
Order By: Relevance
“…As a matter of fact, our idea resides in that the visual scanning is a behavior directed by the driving task, as a combination of top-down and bottom-up influences; this has been widely accepted in literature [3]. As discussed above and, as commonly known in relevant research [1], the visual scanning behavior plays a very important role in performing a sensorimotor task (such as driving), this paper calculates how much correlation there exists between visual scanning efficiency and driving performance, as an evaluation of the proposed VSE .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a matter of fact, our idea resides in that the visual scanning is a behavior directed by the driving task, as a combination of top-down and bottom-up influences; this has been widely accepted in literature [3]. As discussed above and, as commonly known in relevant research [1], the visual scanning behavior plays a very important role in performing a sensorimotor task (such as driving), this paper calculates how much correlation there exists between visual scanning efficiency and driving performance, as an evaluation of the proposed VSE .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the entropy based measures express the concept of complexity, which is essentially different from our proposed VSE . Concretely, GTE is a powerful estimator of the complexity for transition pattern [1] [2], but not of the efficiency for the whole visual scanning procedure. Similarly, SGE [13] and EoFS [12] give the complexity for spatial patterns of fixations and of fixation sequences, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of scanpaths has gained renewed interest in recent years, for example, to study cognitive function [ 7 , 8 ], personality traits [ 9 , 10 ], or as marker in gaze-based applications [ 11 ]. In particular, information-theoretic measures have become a popular tool for studying cognitive function through the analysis of human gaze behavior [ 5 , 8 , 12 , 13 , 14 , 15 , 16 , 17 ]. A commonly used measure is the (gaze) transition entropy (GTE) [ 17 ], which uses a conditional Shannon Entropy [ 18 ] to describe the regularity of transitions between fixations of pre-defined areas of interest (AOI) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low GTE—and thus a low remaining uncertainty about the location of the next fixation given the previous one—thereby is interpreted as a high predictability of the next fixation [ 5 ]. GTE has been applied in various studies (see [ 5 ] for a review), which have shown that changes in GTE are associated with higher task demand [ 13 , 19 , 20 ], increased anxiety [ 21 , 22 , 23 ], or sleep deprivation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%